ANTI-OXIDANT EFFECTS OF POMEGRANATE JUICE ON SACCHAROMYCES CEREVISIAE CELL GROWTH - Aslan, Abdullah; Can, Muhammed Ismail; Boydak, Didem (African Networks Ethnomedicines, 2014)
Background: Pomegranate juice has a number of positive effects on both human and animal subjects. Material and methods: Four groups were used in this study. i: Control group, ii: H2O2 group, iii: Pomegranate juice (PJ) group and iv: PJ + H2O2 group. Following the sterilization method for pomegranate juice (10%) and H2O2 (6% v/v), Saccharomyces cerevisiae cultures were added and the cultivation incubated at 35 degrees C for 72 hours. Fatty acids and vitamin concentrations were measured using HPLC and GC and the total protein bands profile were determined by SDS-PAGE. Results: According to our results statistically significant differences have been determined among the study groups in terms of fatty acids and vitamin (p<0,05). Fatty acid synthesis, vitamin control and cell density increased in groups to which PJ was given in comparison with the control group (p<0,05). Pomegranate juice increased vitamins, fatty acids and total protein expression in Saccharomyces cerevisiae in comparison with the control. Conclusion: Pomegranate juice has a positive effect on fatty acid, vitamin and protein synthesis by Saccharomyces cerevisiae. Accordingly, we believe that it has significantly decreased oxidative damage thereby making a positive impact on yeast development.
Keywords: Pomegranate juice; SDS-PAGE; fatty acid; vitamin